Time evolution of donor activation at low temperatures with co-implantation of phosphorus and hydrogen in silicon. (April 2023) - Lee, Bo-Wen; Lin, Jui-Chang; Chang, Ruey-Dar; Chu, Che-Men; Woon, Wei-Yen
Abstract: We report on the study of the donor activation behavior at low temperatures using subamorphizing implantation of phosphorus and hydrogen to develop three-dimensional integrated circuits. We show that the activation efficiency of phosphorus 0° implantation angle is superior to that at 7° due to the broad defect and donor profiles. At 370 °C, the carrier concentration was enhanced by hydrogen co-implantation at a dose of 10 15 cm −2 . However, the enhancement quickly decayed, and the carrier concentration at 400 °C was lower than that in the sample without hydrogen. The change in the activation behavior suggests that the enhancement in the carrier concentration was due to the defect complexes generated by hydrogen implantation. By eliminating defect complexes, the passivation of phosphorus by hydrogen atoms became evident. At 500 °C, hydrogen caused phosphorus deactivation at the beginning of the annealing process. The carrier concentration then recovered, indicating dehydrogenation during further annealing. Highlights: Phosphorus activation at an implantation angle of 0° angle is better that at 7°. High-dose hydrogen co-implantation enhances the carrier concentration at the beginning of annealing at 370 and 400 °C. Passivation of phosphorus by hydrogen was observed during extended annealing at 400 °C. Two donor activation mechanisms associated with hydrogen co-implantation were observed.